Is territory defence related to plumage ornaments in the king penguin Aptenodytes patagonicus? - Viera, Vanessa; Nolan, Paul M.; Côté, Steeve D.; Jouventin, Pierre; Groscolas, René (Ethology, 2021)
Colourful ornaments in monogamous birds may be directed at potential mates or other conspecifics to signal individual condition, reproductive status or fighting ability, especially in monogamous and territorial species. We investigated whether the size of the orange auricular patch may be an indicator of aggressiveness in the king penguin Aptenodytes patagonicus, a monogamous and territorial seabird. The relationship between auricular patch size and defence behaviour was explored relative to territory location (centre vs. periphery of the colony), period of reproduction (early vs. late), state of reproduction (incubation vs. brooding) and sex. The proportion of time spent in territorial defence and the rate of aggressive behaviours were positively correlated with auricular patch size, mainly because central birds were more aggressive than peripheral birds and also had larger patch sizes. The period of reproduction, state of reproduction and sex did not interact with patch size to affect aggressiveness. Our results suggest that the size of the auricular patch in king penguins may be a reliable signal allowing individuals to evaluate the quality of mates or competitors in terms of aggressiveness. Whether aggressiveness is directly linked to patch size or indirectly through body condition, however, remains to be determined. In any event, birds with larger patches seem to gain central territories in the colony, thereby increasing their reproductive success. Finally, our study adds to the growing evidence that the evolution of sexually monomorphic ornaments may stem from mutual sexual selection.